2015
DOI: 10.1016/j.bbrc.2015.04.127
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Zn superoxide dismutase and the proton ATPase Pma1p of  Saccharomyces cerevisiae

Abstract: In eukaryotes, the Cu/Zn containing superoxide dismutase (SOD1) plays a critical role in oxidative stress protection as well as in signaling. We recently demonstrated a function for S. cerevisiae Sod1p in signaling through CK1γ casein kinases and identified the essential proton ATPase Pma1p as one likely target. The connection between Sod1p and Pma1p was explored further by testing the impact of sod1Δ mutations on cells expressing mutant alleles of Pma1p that alter activity and/or post-translational regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…In response to glucose, sod1 Δ cells exhibit more rapid rates of intracellular acidification, indicating that glycolysis is more active compared to WT cells. In contrast, sod1 Δ cells exhibit a diminished rate of realkalization, indicating that Pma1 is less active in response to glucose, which is consistent with prior work that found that sod1 Δ cells exhibit a defect in Pma1 activity ( 16 , 46 ). To rule out that the intracellular acidification phase is affected by Pma1-dependent realkalization, glucose-dependent changes in intracellular pH were monitored in a strain expressing a hypomorphic allele of PMA1, pma1-tap , containing a C-terminal tandem affinity purification (TAP)-tag ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 89%
“…In response to glucose, sod1 Δ cells exhibit more rapid rates of intracellular acidification, indicating that glycolysis is more active compared to WT cells. In contrast, sod1 Δ cells exhibit a diminished rate of realkalization, indicating that Pma1 is less active in response to glucose, which is consistent with prior work that found that sod1 Δ cells exhibit a defect in Pma1 activity ( 16 , 46 ). To rule out that the intracellular acidification phase is affected by Pma1-dependent realkalization, glucose-dependent changes in intracellular pH were monitored in a strain expressing a hypomorphic allele of PMA1, pma1-tap , containing a C-terminal tandem affinity purification (TAP)-tag ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 89%
“…The reaction mixture was incubated in a boiling water bath for 15 min, and the mixture was cooled afterwards. The extracts were used to detect malondialdehyde (MDA) by measuring the absorbance at 532 nm [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, sod1 Δ cells exhibit slightly diminished rates of re-alkalization, indicating that PMA1 is less active in response to glucose. Indeed, prior work found that sod1 Δ cells exhibit a defect in PMA1 activity (16, 45). To rule out that the intracellular acidification phase is unaffected by PMA1-dependent re-alkalization, glucose-dependent changes in intracellular pH were monitored in a strain expressing a hypomorphic allele of PMA1, pma1-tap , containing a C-terminal tandem affinity purification (TAP)-tag ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%